2017
DOI: 10.3892/ol.2017.6164
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin inhibits canine mammary carcinoma in vitro by targeting cancer stem cells

Abstract: Abstract. Salinomycin (SAL), a polyether ionophore antibiotic, has been demonstrated to selectively kill cancer stem cells (CSCs) in various types of human tumor. The aim of the present study was to investigate the effects of SAL on canine mammary CSCs. CSCs in canine mammary carcinoma cell lines (CMT7364 and CIPp) were identified using a sphere formation assay and flow cytometry. The chemoresistance, invasive potential and expression of stem cell-associated proteins of these spheres was then analyzed. This de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Several studies with HBC cell lines demonstrated that salinomycin inhibits in vitro growth by inducing apoptosis and selectively targeting CSC ( 412 419 ). Likewise, salinomycin was found to have a profound effect in CMC cell lines by selectively depleting canine mammary CSC and inhibiting the Wnt/β-catenin signaling pathway (preventing cell invasion and migration) ( 420 , 421 ).…”
Section: Other Adjuvant Therapiesmentioning
confidence: 99%
“…Several studies with HBC cell lines demonstrated that salinomycin inhibits in vitro growth by inducing apoptosis and selectively targeting CSC ( 412 419 ). Likewise, salinomycin was found to have a profound effect in CMC cell lines by selectively depleting canine mammary CSC and inhibiting the Wnt/β-catenin signaling pathway (preventing cell invasion and migration) ( 420 , 421 ).…”
Section: Other Adjuvant Therapiesmentioning
confidence: 99%
“…Drug repurposing has become an attractive approach due to the known pharmacological and pharmacokinetic properties of approved drugs [4, 5]. Ivermectin is a well-known anti-parasitic agent used to treat a variety of canine parasitic infestations.…”
Section: Introductionmentioning
confidence: 99%
“…Spheres derived from CF41.Mg cells exhibit stemness features such as chemoresistance to doxorubicin and paclitaxel, auto-renewal and high expression of CD44 + /CD24 -/low phenotype (Torres et al 2015). In this regard, the literature indicates that spheres from different canine mammary tumor cell lines exhibit common stemness characteristics as already described (Michishita et al 2011, Rybicka and Krol 2016, Du et al 2017. Therefore, CF41.Mg--spheres are a good model for studying CSC in response to several cytotoxic agents.…”
Section: Discussionmentioning
confidence: 73%